Electronic government 10th IFIP WG 8.5 international conference, EGOV 2011, Delft, The Netherlands, August 28-September 2, 2011. proceedings - EGOV (Conference) 2011 Delft, Netherlands); Janssen, Marijn; Scholl, Hans J.; Wimmer, Maria A.; Tan, Yao-hua.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 10th International Conference, EGOV 2011, held in Delft, The Netherlands, in August/September 2011. The 38 revised full papers presented were carefully reviewed and selected from 84 submissions. The papers are organized in topical sections on foundations, acceptance and diffusion, governance, openess and institutions, architecture, security and interoperability, transformation, values and change.
Electronic reproduction.
Keywords: Internet in public administration -- Congresses; Electronic government information -- Congresses; Electronic books